Global SUMO Proteome Responses Guide Gene Regulation, mRNA Biogenesis, and Plant Stress Responses - Mazur, Magdalena; Van Den Burg, Harrold A. (Frontiers in Plant Science, 2012)
Small Ubiquitin-like MOdifier (SUMO) is a key regulator of abiotic stress, disease resistance, and development in plants. The identification of >350 plant SUMO targets has revealed many processes modulated by SUMO and potential consequences of SUMO on its targets. Importantly, highly related proteins are SUMO-modified in plants, yeast, and metazoans. Overlapping SUMO targets include heat-shock proteins (HSPs), transcription regulators, histones, histone-modifying enzymes, proteins involved in DNA damage repair, but also proteins involved in mRNA biogenesis and nucleo-cytoplasmic transport. Proteomics studies indicate key roles for SUMO in gene repression by controlling histone (de)acetylation activity at genomic loci. The responsible heavily sumoylated transcriptional repressor complexes are recruited by plant transcription factors (TFs) containing an (ERF)-associated Amphiphilic Repression (EAR) motif. These TFs are not necessarily themselves a SUMO target. Conversely, SUMO acetylation (Ac) prevents binding of downstream partners by blocking binding of their SUMO-interaction peptide motifs to Ac-SUMO. In addition, SUMO acetylation has emerged as a mechanism to recruit specifically bromodomains. Bromodomains are generally linked with gene activation. These findings strengthen the idea of a bi-directional sumo-acetylation switch in gene regulation. Quantitative proteomics has highlighted that global sumoylation provides a dynamic response to protein damage involving SUMO chain-mediated protein degradation, but also SUMO E3 ligase-dependent transcription of HSP genes. With these insights in SUMO function and novel technical advancements, we can now study SUMO dynamics in responses to (a)biotic stress in plants.